What do we know about the future of energy and food systems? - Arndt, Channing (International Food Policy Research Institute, 2025)
The global energy transition currently in process involves increases in variable renewable energy generation and ongoing electrification of transport and industrial processes, leading to the possibility of absolute declines in the use of coal and petroleum before 2030.